Relationship between urban spatial structure and carbon emissions: A literature review. (November 2022) - Hong, Shunfa; Hui, Eddie Chi-man; Lin, Yaoyu
Highlights: Collections of basic research for urban spatial planning. Literatures of urban agglomerations, urban size, urban compactness, and urban form on carbon emission. Urban spatial structure and carbon emissions research from a multi-ecosystem interaction framework. Abstract: Carbon emission reduction is one of the key factors in global climate change and should be an important component in urban planning and management. A full understanding of the relationship between carbon emissions and urban spatial structure is necessary. This paper presents the research on this relationship from the perspectives of urban agglomeration, urban size, urban compactness, and urban form. The results revealed that: (1) there is still a lack of research on the spatial structures of urban agglomerations and their relationship with carbon emissions, so it is urgent to conduct indicators system design and empirical research; (2) two-dimensional indicators have frequently been used to describe urban form and urban compactness, but three-dimensional indicators, such as volume ratio and floor height, are also important indicators for policymaking; (3) higher urban complexity, irregularity, and fragmentation were believed to contribute to urban carbon emissions because of the lack of continuity and connectivity. This paper also proposes a comprehensive analytical framework for examining urban spatial structures and carbon emissions. We position the research on the relationship between urban spatial structure and carbon emissions as a bridge between human ecosystems and natural ecosystems.